PENGARUH KOMPETENSI DAN MOTIVASI TERHADAP KINERJA GURU DENGAN ORGANIZATION CITIZENSHIP BEHAVIOR SEBAGAI VARIABEL INTERVENING PADA SMK NEGERI 15 PANDEGLANG - Ihyamukti, Ghaznawie (Jurnal Bisnis dan Kewirausahaan, 2024)
This research aims to investigate the influence of competence and motivation on teacher performance at SMK Negeri 15 Pandeglang, as well as examining the role of Organizational Citizenship Behavior (OCB) as an intervening variable in this relationship. The research method uses a quantitative approach by collecting data through questionnaires distributed to teachers at SMK Negeri 15 Pandeglang. With a population and sample of 40 people. The results of data analysis using SmartPLS version 4 in the research show that competency has no positive effect on employee performance, while motivation has a significant positive effect on teacher employee performance. Apart from that, OCB has also been proven to mediate the relationship between motivation and teacher performance. Meanwhile, competence has not been proven to mediate the relationship between competence and teacher performance. This indicates that not only do competence and motivation directly influence teacher performance, but also through organizational citizenship behavior or OCB. These findings provide an important contribution in the context of human resource development in education, especially in improving teacher performance at SMK Negeri 15 Pandeglang. The practical implications of this research can be used as a basis for schools to design teacher competency and motivation development programs, as well as encourage positive organizational citizenship behavior to improve teacher performance holistically.